Coexistence of blaKPC-IncFII plasmids and type I-E* CRISPR-Cas systems in ST15 Klebsiella pneumoniae - Hu, Yiyi; Jiang, Jianping; Wang, Dongliang; Guo, Qinglan; Wang, Minggui (Frontiers in Microbiology, 2023)
The CRISPR-Cas system in Klebsiella pneumoniae can prevent the entry of blaKPC-IncF plasmids. However, some clinical isolates bear the KPC-2 plasmids despite carrying the CRISPR-Cas system. The purpose of this study was to characterize the molecular features of these isolates. A total of 697 clinical K. pneumoniae isolates were collected from 11 hospitals in China, and tested for the presence of CRISPR-Cas systems using polymerase chain reaction. Overall, 164 (23.5%) of 697 K. pneumoniae isolates had type I-E* (15.9%) or type I-E (7.7%) CRISPR-Cas systems. The most prevalent sequence type among isolates carrying type I-E* CRISPR was ST23 (45.9%), followed by ST15 (18.9%). Isolates with CRISPR-Cas system were more susceptible to ten antimicrobials tested, including carbapenems, compared with the CRISPR-negative isolates. However, there were still 21 CRISPR-Cas-carrying isolates that showed resistance to carbapenems, and these isolates were subjected to whole-genome sequencing. Thirteen of these 21 isolates carried blaKPC-2-bearing plasmids, of which nine had a new plasmid type, IncFIIK34, and two had IncFII(PHN7A8) plasmids. In addition, 12 of these 13 isolates belonged to ST15, while only eight (5.6%, 8/143) isolates belonged to ST15 in carbapenem-susceptible K. pneumoniae carrying CRISPR-Cas systems. In conclusion, we found that blaKPC-2-bearing IncFII plasmids could co-exist with the type I-E* CRISPR-Cas systems in ST15 K. pneumoniae. The mechanism needs to be further studied.